2015
DOI: 10.1021/jacs.5b11317
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Dicupra[10]annulenes

Abstract: Metal-containing aromatic systems (metalla-aromatics) are unique and important both experimentally and theoretically. Among metalla-aromatics, six-membered metallabenzenes and metallabenzynes have attracted much attention in recent years. However, reports on their superior homologues are rare. In this work, the first series of aromatic dicupra[10]annulenes were isolated from the reaction of dilithio reagents and copper salts. Single-crystal X-ray structural analysis revealed dicupra[10]annulenes with averaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 57 publications
2
83
1
Order By: Relevance
“…[217] Relatedt en-p-electron,a romatic dicupra [10]annulenes also have been recently reported. [218] Finally,i ts hould be noted that theoretical studies have suggesteds ome metallacyclobutadienes can also be aromatic. [100,[219][220][221] Scheme21.…”
Section: Metalla-analogues Of Classical Antiaromatic Compoundsmentioning
confidence: 99%
“…[217] Relatedt en-p-electron,a romatic dicupra [10]annulenes also have been recently reported. [218] Finally,i ts hould be noted that theoretical studies have suggesteds ome metallacyclobutadienes can also be aromatic. [100,[219][220][221] Scheme21.…”
Section: Metalla-analogues Of Classical Antiaromatic Compoundsmentioning
confidence: 99%
“…Compared with the chemistry of annulenes and dehydroannulenes, that of metalla‐analogs is much less developed. Reported metallaannulenes or metalladehydroannulenes are mainly small‐ring metallacycles, such as metallacyclobutadienes ( 1 ),, metallabenzenes ( 2 ), dimetallabenzenes ( 3 ), metallabenzynes ( 4 ),, metallacyclooctatetrenes and ten‐membered‐ring dimetallaannulenes ( 5 ),– despite the fact that many polycyclic metalla‐aromatics ( 6 ‐ 11 ) or spiro‐aromatic metallacycles ( 12 ) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Aromaticity is recovered when the 10-MR is forced to be almost planar,a si n1 ,6-methano [10]annulene [24] [the NICS(0) value calculated in the centero fo ne of the two 6-MRs is À14.8 ppm, and that in the centero ft he large1 0-MR is À26.8 ppm].S imilarly,i nar ecent work, Xi and co-workers reported that as eries of synthesized dicupra [10]annulenes, which do not have the H···H stericr epulsion present in trans,cis,trans,cis,cis-cyclodecapentaene, are almostplanar and aromatic. [25] To further confirm the aromaticity of trans,cis,trans,cis,cis-cyclodecapentaene, we performed thef ollowing Gedankenexperiment. We removed these two out-of-plane hydrogen atoms and built the singlet biradical C 10 H 8 .G eometry optimization of this structure leads to closed-shelln aphthalene, whichi sc learly aromatic [NICS(0) = À8.5 ppm in the center of one of the 6-MRs].F or comparison, the same biradical was analyzed in its triplet state, Figure 4).…”
Section: Resultsmentioning
confidence: 99%